European integration, productivity growth and real convergence - Taner M. Yigit; Ali M. Kutan (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2004)
This paper derives a stochastic endogenous growth model that investigates the impact of European Union integration on convergence and productivity growth. We deviate from the general strand of literature by not only deriving a theoretical model for the effects of integration on the rate of economic growth, but also by using more appropriate estimation techniques. The outcome of a series of panel and structural break tests examining the accession process of five recent members to the Union generally show improved rates of productivity growth and convergence to EU standards. We then draw from the experience of these recent members to derive implications for the first-round EU candidate countries. Subsequent tests on the first-round candidate countries find a high level of heterogeneity in growth rates, and a fast-paced convergence to EU standards.
Keywords: 330